THE CORRELATION BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION OF SECOND GRADE STUDENT AT SMA NEGERI 1 TAPUNG HILIR - Atikah Mislin Maslihati; Eliwarti Eliwarti; Rumiri R. Aruan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The purpose of this research was to examine the correlation between vocabulary mastery and reading comprehension of the second grade students at SMA Negeri 1 Tapung Hilir. A correlational designed was used in this research. The sample was 80 students of second grade senior high school selected through using cluster random sampling. In addition, there were two data obtained as part of this research involved the ability of students’ vocabulary mastery and their reading comprehension test score. The test was used to assess students’ vocabulary mastery and reading comprehension. The results showed that the r-observed was 0.699 and the significant value at 0.05, which indicated that there was a correlation between vocabulary mastery and reading comprehension. The R-squared value showed that there were 48.8% of range percentage between students’ vocabulary mastery and reading comprehension. Consequently, it was indicated that the better students’ vocabulary mastery, the higher reading comprehension scores they might obtain.Key words: Correlation, Vocabulary Mastery, Reading Comprehension